C-Reactive Protein as The Predictor of Mortality for COVID-19 Patients in Indonesia - Astari Rahayu Afifah; Phey Liana; Soilia Fertilita; Nelda Aprilia Salim; Verdiansah Verdiansah; Fadhilatul Hilda; Chris Alberto Amin; Tungki Pratama Umar (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Coronavirus Disease 2019 (COVID-19) confirmed cases and deaths continue to rise. When a virus infects the body, the immune system tries to eliminate the virus. C-Reactive Protein (CRP) is a substance produced in the body in response to infection and inflammation. The study aimed to determine the role of CRP in predicting COVID-19 patients’ mortality. From the 1st of March to the 31st of August 2020, data on patients confirmed with COVID-19 were collected from medical records. The correlation between CRP levels and patient mortality was determined using a Chi-Square test. A Receiver Operator Curve (ROC) analysis was used to determine the best CRP cut-off point, and a survival analysis was used to assess the patient outcome. This study included a total of 210 eligible patients. Survivors and non-survivors were divided into two groups of patients (159 patients and 51 patients, respectively). The CRP cut-off was 54 mg/L, with an AUC of 0.817 (p<0.001). C-reactive protein levels were related to COVID-19 patient mortality (p=0.000). According to the survival analysis, patients with CRP levels > 54 mg/L had a lower chance of 30-day survival (p=0.0001). This study presented that CRP levels can be used to predict mortality in COVID-19 patients.